Analisis Potensi Objek Wisata Benteng Marlborough Melalui Penerapan Sapta Pesona di Kota Bengkulu - Yanmesli; Dwiatikah, Iklil Nadiah; Sitompul, Laura Meilisa (Universitas Prof. Dr. Hazairin, S.H, 2025)
This study analyzes the tourism potential of Marlborough Fort in Bengkulu through the implementation of Sapta Pesona. This fort has unique historical and architectural attractions, supported by adequate amenities and good accessibility. However, the facilities and infrastructure of souvenir shops and tour guides need to be improved. The implementation of Sapta Pesona shows good aspects of